2022
DOI: 10.3389/fimmu.2022.836492
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein Expression In Vitro and Hematologic Effects in Mice Vaccinated With AZD1222 (ChAdOx1 nCoV-19)

Abstract: Severe COVID-19 can be associated with a prothrombotic state, increasing risk of morbidity and mortality. The SARS-CoV-2 spike glycoprotein is purported to directly promote platelet activation via the S1 subunit and is cleaved from host cells during infection. High plasma concentrations of S1 subunit are associated with disease progression and respiratory failure during severe COVID-19. There is limited evidence on whether COVID-19 vaccine-induced spike protein is similarly cleaved and on the immediate effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…S1 was detectable via western blot in our severe COVID-19 patient plasma samples only after immunoprecipitation. Similarly, S1 was detectable in the plasma of mice injected with the SP-containing lysate, but not full-length SP (data not shown), consistent with previous findings in mice vaccinated against full-length SP 57 . A serial dilution of recombinant S1 showed that S1 could not be detected at or below 100 ng/ml via our western blot protocol (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…S1 was detectable via western blot in our severe COVID-19 patient plasma samples only after immunoprecipitation. Similarly, S1 was detectable in the plasma of mice injected with the SP-containing lysate, but not full-length SP (data not shown), consistent with previous findings in mice vaccinated against full-length SP 57 . A serial dilution of recombinant S1 showed that S1 could not be detected at or below 100 ng/ml via our western blot protocol (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, her repeat LTT following natural SARS-CoV-2 infection showed reactivity to both ChAdOx1 and NVX-CoV2373 COVID-19 vaccines, the agents which she has never encountered. One hypothesis is that the ChAdOx1 vaccine produced spike protein in vitro as other groups have demonstrated 8 and induced a T-cell-mediated response to the spike protein generated in vitro rather than an allergic response. Similarly, the positive reaction NVX-CoV2373 was suspected to be a T-cell response to the recombinant spike protein in the vaccine after vaccination and previous infection.…”
Section: Discussionmentioning
confidence: 99%
“…Here too however it should be considered that the expression of ACE2 on platelets is still controversial, and ACE2-independent binding of SARS-CoV-2 to platelets has been proposed (55). Moreover, against this hypothesis are the findings that sSP was detected in vaccinated healthy subjects both after ChAdOx1 nCoV-19 and mRNA-1273 vaccines (54,56), and in sera of CD-1 mice injected intramuscularly with ChAdOx1 nCoV-19 without being associated with any catastrophic effects (57). Finally, several VITT patients subsequently developed COVID-19 (58).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…55 Moreover, against this hypothesis are the findings that sSP was detected in vaccinated healthy subjects both after ChAdOx1 nCoV-19 and mRNA-1273 vaccines, 54 56 and in sera of CD-1 mice injected intramuscularly with ChAdOx1 nCoV-19 without being associated with any catastrophic effects. 57 Finally, several VITT patients subsequently developed COVID-19 58 and given that in COVID-19 patients circulating sSP protein is found, 59 the lack of VITT recurrence as an anamnestic response in these patients does not support the hypothetical role of vaccine-induced circulating spike for VITT.…”
Section: Pathophysiologymentioning
confidence: 99%